Islamic Nationalism in Pesantren (Study on Pesantren in Pantura Region of Central Java) - Moh In'ami; Mualimul Huda; Masrukhin Masrukhin (TSAQAFAH, 2023)
The very idea of ‘Islamic Nationalism’ in Indonesia grounded from educational values and character building in maintain a spirit of unity and brotherhood, participate in realizing security, love for the motherland, and accommodating the nation's culture. In Indonesian pesantren tradition, we found a ‘basic-belief’ grounded from historical facts about ulama’s struggle to maintain harmony but asserting the religious spirit for nationalism. This study covering Islamic boarding schools in Central Java: Raudlatul Ulum, Darul Falah, and Futuhiyyah. Using non-structural interviews, we collect several motivations, teachings, and another jargon implemented in sense of pseudo-pedagogical and political education. We analize interpretively focusing the ‘basic-belief’ of their ‘hubb al-wathan’ as basis of our coined ‘islamic nationalism’ in daily life. This study show that these boarding schools have a commitment jargon with several activities supported ‘islamic nationalism’ as well as students training on responsibility, discipline, independence, mutual cooperation integrity using several platform as follows: commemoration of Islamic holidays, traditions of deliberations, bahtsul masail forums, participation in general elections, social service activities, raising aid for social solidarity, commemorating the Republic of Indonesia's independence day, Hari Pahlawan, hari Pancasila, Hari Santri and another activities. The involvement of students in educational activities can train the readiness of students to take part in caring for national commitment, the spirit of diversity, tolerance, and accommodation for the nation's culture and create harmony.